Carbon Sequestration of Above Ground Biomass Approach in the Rehabilitated Mangrove Stand at Jepara Regency, Central Java, Indonesia - Arif Noor Hayati; Norma Afiati; Supriharyono; Muhammad Helmi (Faculty of Fisheries and Marine Universitas Airlangga, 2023)
Highlight Research Mangrove rehabilitation area has a better potential for carbon sequestration The more trees that grew and developed with a large DBH size the more affected the biomass, carbon content and carbon sequestration of mangroves. Among the four species studied, mucronatais characterized by highest carbon density storage Temperature and salinity affect the value of mangrove biomass, carbon content, and carbon sequestration Abstract Among its many advantages, mangroves have a function as carbon sequestration and storage. The aim of this study was to determine the differences in the ability of various rehabilitated mangrove species of carbon Sequestration of Above-Ground Biomass. This study was conducted from June 2020 to December 2021 in Kedung, Mlonggo, and Keling Subdistricts, Jepara Regency, Central Java, Indonesia. The mangrove plantation was a result of a rehabilitation programme sponsored by a society and the local government since 2009. Carbon sequestration measurement in tree biomass was estimated by a non-destructive method i.e., by measuring the Diameter at Breast Height (DBH). Statistical analysis to determine the relationship between carbon storage in several species of mangroves and the environmental factors were performed using XL stat 2022. There were 4 (four) mangrove species found i.e., Avicennia marina (Forssk) Vierh, Rhizophora apiculata (Blume), Rhizophora mucronata (Lamk), and Sonneratia alba Sm. The highest CO2 absorption (397.21 tons ha-1) was obtained both in Kedung and Mlonggo stations with R. mucronata, whereas in Keling station with R. apiculata the absorption was 54.27 tons ha-1. The results of Principal Component Analysis (PCA) showed that the number of trees and DBH had a relationship with biomass, carbon content, and carbon absorption. Diameter at Breast Height in mangrove species can be used as indicators to assess carbon sequestration in Above Ground Biomass.